Combined heat and power units and network expansion planning considering distributed energy resources and demand response programs - Qaeini, Saeed; Nazar, Mehrdad Setayesh; Varasteh, Farid; Shafie-khah, Miadreza; Catalão, João P.S. (Elsevier, 2020)
This paper addresses a hierarchical framework for the energy resources and network expansion planning of an Energy Distribution Company (EDC) that supplies its downward Active Industrial MicroGrids (AIMGs) with hot water and/or steam and electricity through its district heating and electric grid, respectively. The main contribution of this paper is that the proposed model considers AIMGs’ electricity transactions with each other and/or other customers through the EDC’s electric main grid and investigates the impacts of these transactions on the expansion planning problem. The solution methodology is another contribution of this paper that tries to trade-off between accuracy and computational burden. The proposed framework uses a three-stage iterative heuristic optimization algorithm that considers different uncertainties of the planning and operational parameters. At the first stage, the algorithm determines the characteristics of energy system facilities for different stochastic parameter scenarios. At the second stage, the feasibility and optimality of AIMGs’ electric transactions are evaluated and the optimal scheduling energy resources in normal states are determined. Finally, at the third stage, different demand response alternatives, load shedding and the AIMGs’ electric transaction interruptions for contingent conditions are decided. The proposed method is applied to 9-bus, 33-bus and 123-bus IEEE test systems. Further, a full search algorithm is used to evaluate the quality of solutions of the proposed algorithm. The introduced algorithm reduced the total costs for the 9-bus, 33-bus and 123-bus system about 18.645%, 9.658%, and 4.849% with respect to the costs of custom expansion planning exercises, respectively.
Keywords: production of electricity; costs; optimisation; energy production (process industry); electrical power networks; power plants; district heating; electricity; distribution of electricity; electricity consumption; fi=Sähkötekniikka|en=Electrical Engineering|